2023
DOI: 10.1057/s41267-022-00589-5
|View full text |Cite|
|
Sign up to set email alerts
|

International business and Africa: Theoretical and applied challenges, and future directions

Abstract: In response to Nachum et al.’s (J Int Bus Stud, 2023) call for further research in Africa by international business (IB) scholars, we argue that while IB scholars may have been slow to engage with Africa, the same cannot be said of related and IB-relevant business and management scholarship. There is already a substantial body of work on Africa in other domains of business and management scholarship – and relevant theorizing – that represents an important resource for IB scholarship. In contextualizing the ‘in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Firms collaborate with academics and universities to appear "socially responsible" by addressing societal problems through these partnerships (Ankrah and Al-Tabbaa 2015). In doing so, international firms fulfill their transformational role in sub-Saharan Africa, supporting the notion of Africapitalism (Kamoche and Wood 2023). This finding implies that international firms enhance their image, reputation, and legitimacy in the eyes of stakeholders by associating with business school academics.…”
Section: Knowledge Content From Business School Academics' Knowledge ...mentioning
confidence: 79%
“…Firms collaborate with academics and universities to appear "socially responsible" by addressing societal problems through these partnerships (Ankrah and Al-Tabbaa 2015). In doing so, international firms fulfill their transformational role in sub-Saharan Africa, supporting the notion of Africapitalism (Kamoche and Wood 2023). This finding implies that international firms enhance their image, reputation, and legitimacy in the eyes of stakeholders by associating with business school academics.…”
Section: Knowledge Content From Business School Academics' Knowledge ...mentioning
confidence: 79%
“…The study responds to the call for more research on Africa‐to‐Africa Internationalization (Owusu‐Yirenkyi et al, 2023) by investigating how technological innovation, particularly through AI, influences the expansion strategies of new ventures in the African context. It addresses the scarcity of comprehensive studies in formal sectors within Africa (Kamoche & Wood, 2023), offering insights into the role of technology‐driven ventures in shaping the continent's global business presence (Farinloye et al, 2024; Owusu‐Yirenkyi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The present research was prompted by a recognition of both the increasing attention devoted to global business strategies and the digital revolution sweeping across industries (Chalmers et al, 2021; Dwivedi et al, 2021; Loureiro et al, 2021) and playing an increasingly integral role in international business by enhancing efficiency and introducing complexity in business simultaneously (Chen et al, 2022). Notably, the majority of studies in this realm have predominantly centred on developed countries, leaving a critical void in our understanding of the unique challenges faced by emerging economies in implementing AI practices (Kamoche & Wood, 2023) and the call for exploring more of Africa‐to‐Africa Internationalization (Owusu‐Yirenkyi et al, 2023). Moreover, in the African context, while an increasing body of research has been focusing on digital technologies within the informal market (Boafo et al, 2022; Boafo et al, 2023; Dana & Ratten, 2017), there is a notable scarcity of comprehensive studies addressing the formal sectors (Mogaji & Nguyen, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These are key to the effective development, growth and sustainability of EMNCs in emerging markets. This combination of both flexibility and resilience, and an ability to improvise in turbulent, institutionally ambiguous—even dysfunctional and weak—regulatory environments in Africa, is supported by the work of Cooke et al (2015), Kamoche and Wood (2022), Munene (1991) and Nachum et al (2022), and has been identified as a fruitful avenue for further research (Cunha et al, 2022).…”
Section: Local Employment Labour Markets and Human Resourcesmentioning
confidence: 95%
“…With 54 countries, Africa is culturally and ethnically diverse, socio-economically heterogenous and a politically complex continent, offering significant opportunities for foreign direct investment increasingly from Asia as well as research in international business and management. Whilst some observers argue that Africa has been relatively neglected particularly in international business (e.g., Nachum et al, 2022; Zoogah et al, 2015), others point to significant developments in related management fields (Kamoche & Wood, 2022). Traditionally, the dominant interest has been Western MNCs and the suitability of western management practices.…”
Section: Introductionmentioning
confidence: 99%